STUDI KASUS: PENERAPAN TERAPI RELAKSASI OTOT PROGRESIF UNTUK MENGATASI GANGGUAN TIDUR PADA LANSIA DI SENTRA TERPADU PANGUDI LUHUR BEKASI - Dewi, Mia Kusuma; Andas, Amzal; Puspitasari, Indah; Wada, Fauziah H; Romantika, I Wayan; Shoaliha, Maratun; Nurwahidah, Andi Tenri (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background : Indonesia is currently experiencing a period of demographic growth, moving from a high birth rate to a low birth rate as well as death. so that the elderly population in the future will increase. For the elderly who experience health problems in terms of physical, psychological. This will have an impact on the sleep quality of the elderly. Non-pharmacological methods can be carried out by implementing behaviors that target thoughts, feelings that worsen sleep quality, namely progressive muscle relaxation therapy that does not require technology, costs, special equipment, does not require a special place and time, and is easy to learn so that researchers are interested in conducting studies. case. The aim is to determine the effect of progressive muscle relaxation therapy in the elderly who experience sleep disturbances. Methods: The sample in the case study was based on the results of screening using the SQS Single item and was selected based on inclusion criteria, namely >60 years. The number of samples that met the criteria were 5 elderly people. Data was collected through observation and interviews. Data analysis was carried out by identifying patterns, comfort and effects during sleep disturbance. In this study, data were analyzed to determine the effectiveness of progressive muscle relaxation therapy to treat sleep disturbances in the elderly. Results: This case study shows that after 5 days of therapy, the sleep quality score results from a total score of 15 (poor) the score becomes 36 (good). This shows that progressive muscle relaxation therapy can be an effective alternative non-pharmacological treatment to treat sleep disorders in the elderly. Conclusion Progressive muscle relaxation therapy can be used as an effective treatment option in reducing sleep disturbances in the elderly.